Recursos tecnológicos utilizados para la enseñanza de matemáticas con estudiantes de la Unidad Educativa Velasco Ibarra periodo 2021-2022. - Puculpala Guambo, Miryam Janneth (2022)
The COVID-19 pandemic that the country has had to face since March 2020, forced people to live in confinement, having to suspend many face-to-face activities. where the education sector has been one of the most affected, requiring a radical transformation at the pedagogical and social level, generating new teaching scenarios giving way within the virtual spaces to teleducation, This research aims to determine the technological resources used in teaching, to carry out this purpose was supported by 34 students and the mathematics teacher of the educational unit "Velasco Ibarra "a survey was applied with structured questions with a questionnaire as an instrument, aimed at math teachers and students of 8 items each , with this was possible to obtain informative data, which have the following aspects as the use of technology resources by the student, the application of microsoft teams, In the teaching of teachers it should be noted that for the resolution of exercises and development of his class works mostly with resources such as slides and virtual whiteboards, research is supported by bibliographical sources to reinforce all concepts, definitions, of technological resources and thus meet the first specific objective that was to conceptualize information about Technological resources in education, The research was descriptive, and bibliographic it can be concluded that the teacher for the teaching of mathematics uses the technological resources like the digital platforms of microsoft teams and zoom .